Financial Governance Training in MSME Business, Towards a Resilient Business - Aan Masamah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
Financial governance in business activities is a necessity, whether small, medium or large scale businesses. Managed business finances can help improve sales performance and key business units. In financial management, actual information is obtained and is connected to various business interests, especially income/wealth. Against this background, this service activity aims to share knowledge and ways to manage business finances, so that they can strengthen the business they are doing. The method used in this activity is explanation and practice. The participants of the service activity are MSME business actors in the Rangkasbitung District, Lebak-Banten. The number of participants was 25 people, consisting of women and men. The results of the activities are in the form of knowledge provision and applications for making financial reports. The participants were also taught starting from the early stages, namely from the stages of making transaction journals, posting, recapitulation, making financial reports, and making infographics.